Prepropriate analysis of time series by methods of fractal analysis and phase trajectories - Antonova, Iryna Vladimirovna; Chikina, Natalia Aleksandrovna (НТУ "ХПІ", 2018)
The procedure of the qualitative analysis of time series, for which the hypothesis of trend existence isn’t confirmed, with application of the methods of nonlinear dynamics and the theory of chaos, is presented. The real time series characterizing prevalence of various skin diseases in Ukraine are considered. The basis for similar researches is Takens’s theorem. The randomness of the studied dynamical system given by time realizations is established by means of Lyapunov’s indicator. The state stability is estimated by Hausdorf’s fractal dimension and the fractality index. Visual evaluation of the time series was carried out by means of the phase trajectory restoration procedure. As a result of the analysis of phase pointsin the phase space the split attractor is indicated, which gives the chance to speak about its bifurcation.

Запропоновано процедуру якісного аналізу часових рядів, для яких не підтверджується гіпотеза про наявність тренда, із застосуванням методів нелінійної динаміки, теорії хаосу. Розглянуто реальні часові ряди, що характеризують поширення різних шкірних захворювань в Україні. Обґрунтуванням для подібних досліджень є теорема Такенса. Хаотичність досліджуваної динамічної системи, що задана часовими реалізаціями, встановлена за допомогоюпоказника Ляпунова. Оцінка стійкості стану оцінювалась фрактальною розмірністю Хаусдорфа і індексом фрактальності. Візуальна оцінка часового ряду проводилась за допомогоюпроцедури відновлення фазових траєкторій. В результаті аналізу фазових точок фазового простору виявлено розщеплений атрактор, що дає можливість говорити про його біфуркацію.
Предпрогнозний аналіз часових рядів методами фрактального аналізу та фазових траєкторій
Keywords: qualitative analysis; theory of chaos; Lyapunov’s indicator; fractal dimension; fractality index; phase space; якісний аналіз; методи нелінійної динаміки; теорія хаосу; показник Ляпунова; фрактальна розмірність; індекс фрактальності